Curadoria e preservação digital: diretrizes para a gestão de dados científicos - Viviane Lílian dos Santos Barrozo (2022)
The digital transformations that took place in the second half of the 20th century had a great impact on scientific practice and raised a reflection on the use of information in digital environments. The increase in the production and consumption of data in digital format has reached a level of prominence for science and reinforced the importance of digital curation and preservation, whether for immediate or long-term access. Thus, the preservation of digital objects has been one of the great challenges in contemporary times, since it needs to resort to methods and technologies that integrate the physical (storage), logical (format) and intellectual aspects of these objects. This research aims to recommend the use of digital preservation principles and guidelines to support a digital preservation policy at the Federal University of Minas Gerais. Methodologically, the study is characterized as being of an applied nature and of a qualitative approach. As for the objectives, the research is exploratory and explanatory and, as for the technical procedures, it is bibliographical, documentary and field. The investigation took place in four phases: the first consisted of the theoretical framework, about digital curation and preservation; the second resorted to the application of a semi-structured questionnaire to diagnose the practices of researchers, characterized as producers/consumers of scientific data, and the level of preservation of scientific data; in the third, the semi-structured interview was applied to know the practices of the interviewees regarding the production and/or consumption of scientific data; finally, the fourth phase included documental research, through the appreciation of institutional documents (plans, policies, reports, manuals, projects and resolutions) of the institution, in order to identify aspects of digital governance. The study identified the practices of researchers regarding data sets and institutional actions regarding this type of governance. The analysis showed that researchers deal with heterogeneous and singular data, of different types and supports, and, in many cases, saved in formats that are inappropriate for preservation and without documentation and metadata appropriate to the disciplinary domains. Most of the data is hosted in the cloud (outsourced service), through restricted access and paid for by the researcher, or stored on personal equipment or fragile media, without monitoring, migration and due technological updating. It was identified the need to improve the practices of these researchers in terms of data sets, to supply the lack of guidelines with the provision of instruments, guides and plans and to support them in terms of data services with the help of a specialized team composed of librarian, in addition to encouraging the use of technological resources equipped with an adequate information technology infrastructure, already offered by the university. Thus, the preservation of scientific data was identified and a set of principles and guidelines was indicated that can serve as a mechanism to support the university in implementing its digital preservation policy. It is hoped that this study will prompt a reflection on the improvement of data management practices and, above all, ratify the importance of institutional commitment to research. With this, the digital preservation policy is formalized, with a view to safeguarding scientific data sets and making them available for reuse and, in this way, contributing to the advancement of Brazilian science.